2006
DOI: 10.1051/0004-6361:20054455
|View full text |Cite
|
Sign up to set email alerts
|

The UV spectrum of HS 1700+6416

Abstract: Aims. In preparation of a study of the He ii/H i ratio towards the bright QSO HS 1700+6416, we predict the metal line content of the far-UV spectral range by modelling 18 metal absorption line systems with redshifts 0.2 < z < 2.6 identified in the spectrum of this quasar. Methods. For that purpose, we investigate the spectral energy distribution of the metagalactic ionizing radiation field. Simple photoionization models based on 8 different shapes of the ionizing background are tested for each system. The adop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 50 publications
3
36
0
Order By: Relevance
“…In the vicinity of z = 1.7193, the η-values reach several hundreds due to a sharp decrease in the number of photons with energies E 4 Ryd in the ionizing continuum and, as a consequence, the impossibility to ionize He ii. At z = 1.1923, where the preferable SEDs return to the range detected between He ii/H i forest studies have shown a slow evolution of η toward smaller values at lower redshift, with the meanη ∼ 70 at z = 2.9 andη ∼ 40 at z = 2.0 (Zheng et al 2004;Fechner et al 2006). Our values are in line with these results.…”
Section: Discussionsupporting
confidence: 91%
“…In the vicinity of z = 1.7193, the η-values reach several hundreds due to a sharp decrease in the number of photons with energies E 4 Ryd in the ionizing continuum and, as a consequence, the impossibility to ionize He ii. At z = 1.1923, where the preferable SEDs return to the range detected between He ii/H i forest studies have shown a slow evolution of η toward smaller values at lower redshift, with the meanη ∼ 70 at z = 2.9 andη ∼ 40 at z = 2.0 (Zheng et al 2004;Fechner et al 2006). Our values are in line with these results.…”
Section: Discussionsupporting
confidence: 91%
“…3. Additionally, the metal lines predicted to arise in the FUSE spectral range (Fechner et al 2006b) are considered during the optimization procedure modifying the χ 2 -estimation (Eq. (1)):…”
Section: Hs 1700+6416mentioning
confidence: 99%
“…This peak is most likely due to strong interstellar C ii λ1036 absorption, which is not considered in the spectrum fit procedure. Furthermore, strong C iv absorption from the Lyman limit system at z = 2.3155 is expected in the UV, which is probably underpredicted (see Fechner et al 2006b). Therefore, we overestimate the amount of absorption due to He ii leading to unrealistically high values of η.…”
Section: Hs 1700+6416mentioning
confidence: 99%
“…We repeated the calculations with different spectra for the ionising background. Using a modified Haardt & Madau spectrum where the helium edge is shifted to 3 Ryd, possibly due to the opacity of higher He ii Lyman series lines (Fechner et al 2006) or a background radiation mainly created by AGN as proposed by Mathews & Ferland (1987), resulted in density parameters that are within each others 1σ error intervals. Misinterpretations in the sample of narrow Lyman α lines could add another uncertainty.…”
Section: Photoionisation Calculationsmentioning
confidence: 99%